De aprendiz a mestre da palavra: tornar-se lia-na'in nos anos de luta e restauração da independência em Timor-Leste (1975-2002) - Keu Apoema (2020)
The present research aims to understand the educational processes of lia-na’in(s), masters or kings of words, in the local language, currently responsible for their sacred houses – from the period of fight for independence from Indonesian occupation in East-Timor (1975-1999) to the Restoration of Independence, proclaimed in 2002, after a brief period of intervention by the UN. The study investigates the learning processes of these masters, taking into account the transformations and ruptures that took place locally during this time, including the resistance, the destruction of sacred houses by Indonesian army, the massive conversion to Catholicism, among other disruptive events. The lia-na’in is the leader and ritual authority of the sacred houses – material and non-material institutions corresponding to lineages, the basis for values and local epistemologies related to lisan, which define the relationships among humans, between humans and non-humans, and between everyone and the divinity Maromak. The work is based on two main sources: first, the testimonies of 18 lia-na’in(s) in the municipality of Ainaro from January to May 2018 – the methodology used was oral history, which approaches their histories of life, the relationship with their respective sacred houses, the narratives about origin, the general aspects about the knowledge that they claim, and the connection of this knowledge and its signals on national identity. Secondly, the study entails an audiovisual archive related to ceremonies of the Restoration of Independence – general cultural elements are present, including the lia-na’in (s) from almost all districts (municipalities). In theoretical terms, the research study is centered in the field of cultural history and anthropology, promoting a discussion about permanence and continuity of historical facts, taking into perspective decolonial logic in approaching local epistemologies. Besides the introduction and conclusion, five chapters illustrates the work. The first chapter promotes a discussion on the theoretical-methodological references of the study, the development of the field and approaches for dada analysis. In the second chapter, there is an introduction to the lisan, conceiving her as the body of local and habitual knowledge with a religious basis, and simultaneously, like in the sacred house, the basis for sustaining such knowledge. The third chapter presents the lia, seen as much as a word as a ritual that describes the continuity of the ceremonial life of the sacred houses during the period of Indonesian occupation. The fourth chapter describes the learning process of lia-na’in through successive participatory stages - from observation to acquisition of authority and power of speech, including an analysis of the relationship between the Catholic Church and the sacred house. The fifth chapter works with the categories related to national identity, like “kultura Timor” and “sacred land”, both present in the testimonies of lia-na’in(s) – seeking to understand how they project the nation through imaginary community of practices. Finally, the study presents an analysis of the first part of the Ceremonies of the Restoration of Independence led by lia-na’in(s) from different municipalities. Throughout the development of the research, one surmises that the learning processes of lia-na’in(s) take place in their participation in knowledge network, which are composed of ties of kingship rooted in the house of origin and other sacred houses and their respective authorities. These processes are possible thank to the engagement, at different levels, in ritual in their sacred houses and others with which they connect through diverse ties of affinity. In the end, the study infers that such learning processes, as well as the production and reproduction of culture, occur in conflict with historical events through strategies of continuity and efforts for legitimizing local everyday practices.